ANALISIS SOSIOLOGIS TERHADAP IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PADA MASYARAKAT INDONESIA - Chairil N. Siregar (Fakultas Seni Rupa dan Desain ITB, 2007)
The program of Corporate Social Responsibility is the social program that provides a lot of contributions in solving social problems in job opportunities, health, education, economy, and the environment. The implementation of the CSR program still faces some obstacles, namely, the program has not been socialized. Another barrier is the difference of viewpoint between the Department of Laws and Human Right and the Department of Industry. The other is that there is no clear regulation on the implementation of CSR. However, CSR program can improve the spirit of togetherness among different communities.